Antara Satu Rumpun dan Satu Keluarga: Kajian Historis-Komparatif terhadap Bahasa Jawa, Batak, dan Bali - Safitri, Ayu; Hendrokumoro (Universitas Negeri Surabaya, 2025)
ABSTRACT This study aims to analyze the kinship between Javanese (BJ), Batak (BT), and Balinese (BB) languages through a comparative historical linguistic approach. These three languages are part of the Austronesian family but have developed in geographically and culturally distinct regions. The research focused on determining the percentage of kinship, the divergence time of the languages, and the presence of cognate vocabulary in the languages. The results show that despite significant differences due to historical and cultural divergence, a number of lexical forms and morphological structures were found, indicating traces of a common origin in Proto-Austronesian. Based on this research, it was also found that (1) Batak language retains its proto-form more than Javanese and Balinese languages. (2) Javanese and Batak languages belong to the same language family, sharing a kinship percentage of 22%. Based on calculations, the two languages diverged between 1305-1985 BC. This study found three types of phonemic correspondences: /i e/, /ǝ ɔ/, and /w b/. Phonetic similarities were also found between the vowels [U u] and [I i]. (3) Javanese and Balinese languages belong to the same family, sharing a kinship percentage of 37%. Based on glottochronological calculations, it was found that the two languages diverged between 185-525 BC. In this study, phonemic correspondences were found between the phonemes /ɔ ǝ/ and /ɔ a/. (4) Balinese and Batak languages belong to the same language family, sharing a kinship percentage of 26%. Based on the calculations, the two languages diverged between 975-1031 BC. This study found one phonemic correspondence /r h/. Key Words: Javanese Language, Batak Language, Balinese Language, Comparative Historical Linguistics, Austronesian